The Effect of Health Information Systems on the Performance of SP2TP Staff in the Padangsidipuan City Region - Elisa Efelinda Siregar; Asriwati Asriwati; Tengku Moriza (Journal La Medihealtico, 2022)
The health information system in several health centers is still being used, but due to problems in several health centers, the activity of reporting on the activities of the health center is hampered. So far, puskesmas activity reports are done manually which can interfere with the performance of data processing staff. The purpose of this study was to analyze the influence of health information systems on the performance of puskesmas staff.=0.05).This type of research is quantitative with cross sectional design. The research was conducted in 10 Community Health Centers in Padangsidimpuan City. The research population was 48 people, and all of them were used as samples. Withdrawal of samples randomly (random sampling). The data were analyzed using univariate, bivariate using chi-square and multivariate using multiple logistic regression at 95% confidence level (The results showed that the performance of Puskesmas staff in managing health information in the Padangsidimpuan City area was influenced by direct information system evidence, information system reliability, system accessibility, and information suitability. Variables that have no effect are information system assurance, information system usability, system content, and information design. The most dominant factor affecting the performance of the Puskesmas staff in the Padangsidimpuan City work area is the information system reliability variable having Exp(B)/OR = 17.836. It is suggested that the puskesmas should send data processing personnel to attend education and training on health information systems. Carry out routine maintenance on the facilities used in data processing so that they do not experience problems.